Inflammatory and linear verrucous epidermal nevus in vulvar region: a differential diagnosis with vulvar condyloma - Chaves, José Humberto Belmino; Guimarães, Julia Espíndola; Eleutério Junior, José (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Inflammatory linear verrucous epidermal nevus (ILVEN) is a variant of verrucous epidermal nevus. It has a psoriasiform or eczematous and itchy aspect, and has differential diagnosis compared to other more common dermatoses; thus, histological studies are often necessary. It mainly affects women of early age and must be differentiated from condyloma acuminatum. Interestingly, the lower left limb is often involved, but the genital region is rarely affected. Treatment is refractory and the best method is not yet established. Objective: We present a case of unusual vulvar involvement known as inflammatory linear verrucous epidermal nevus. Methods: This was a clinical case report of a child diagnosed with ILVEN in the vulvar region. Case report: An 11-year-old female presented to the gynecology department of the Universidade Federal de Alagoas complaining of pruritic lesions on the large left vulvar lip, perianal and anal regions, and vaginal introitus. The lesions were hypochromic, eroded, and covered by scabs along the Blaschko line with verrucous lesions in the abdomen and upper and lower limbs. These characteristics fit the clinical criteria of Altman and Mehregan, and the histological criteria of Dupre and Christol for diagnosis of ILVEN. The treatment was performed with Vitanol A® and Epidrat Ultra® with partial improvement of the lesions. We chose to excise the lesions to control the condition. Conclusion: These lesions are characterized by recurrent inflammatory phenomena including psoriasiform or eczematous aspects in the extremities with genital involvement being rare. Other common dermatoses are often confused with ILVEN and make anatomically pathological analysis extremely important for diagnosis. Despite details on several types of treatment for ILVEN, there are no studies on relative advantages because this lesion is very refractory to the treatment.